A solvothermal method to synthesize fluorescent carbon nanoparticles and application to photocatalysis and electrocatalysis. (19th November 2014) - Hongren, Li; Feng, Li; Aimin, Deng
Abstract A novel solvothermal approach to synthesize fluorescent carbon nanoparticles (CNPs) was developed using glucose and ammonium oxalate as the carbon source, and glycol as the solvent. The solution of as‐prepared CNPs emitted blue‐green fluorescence under ultraviolet (UV) light at 365 nm, and the carbon nanoparticle formation was investigated through XRD, TEM, DLS, FT‐IR, UV, PL, XPS. The particle was well dispersed with an average diameter of about 10–30 nm. In contrast with previous methods, in this synthesis process neither strong acid treatment nor further surface modification was necessary. The solution of as‐prepared CNPs were applied to photocatalytic degradation of mountain green in the present H2O2, and the decolorization rate was over 97% when the reaction time was more than 7 h under visible light. The as‐prepared CNPs were also applied to electrocatalysis and showed excellent electrocatalytic activity. Copyright © 2014 John Wiley & Sons, Ltd.